Inflation Threshold Effect on Economic Growth in Turkey - ESEN, Ömer; AYDIN, Celil; AYDIN, Recai (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
In this study, the role of inflation threshold effect on economic growth has been investigated for Turkey in the 2002:Q1 – 2015:Q1 period. At the first stage, inflation threshold value has been detected. After that, inflation-economic growth relation has been examined using threshold autoregressive (TAR) model. Results indicate that there is a nonlinear relationship between inflation and growth rate; the threshold for the influence of inflation on economic growth is 8.89%; and an inflation rate above this threshold has a negative influence on economic growth while an inflation rate below this threshold has a positive influence on economic growth. In this regard, it is important to achieve sustainable growth, which plays a crucial role in increasing the efficiency of implemented monetary policies and assuring stability. Therefore, political and economic decision-makers should not ignore the concept of threshold within the scope of monetary policy while determining the target inflation rate in their efforts to deal with inflation.